2016
DOI: 10.11648/j.ajss.20160405.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resisted Sprint Training on Sprint Performance in High School Baseball Players

Abstract: Abstract:Resisted sprint training (RST) affects sprint speed in the acceleration phase, but there is no research regarding this for in adolescents. This study investigated the effects of RST on sprint speed and ground reaction force (GRF) in high school baseball players. Subjects were assigned to the resisted sprint group (RSG, n=10, loading 20% body mass), or the normal sprint group (NSG, n=9, without loading) and trained three days per week for eight weeks. Sprint speed [0-5, 5-10, 10-15, 15-20 and 0-20 mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The results of this study demonstrate that BRS training is most beneficial in improving athletic performance in youth boys. Although previous studies using FRS training programmes have reported improvements in sprinting performance using loads ≤ 20% BM (2,31,36), the aim of this study was to evaluate the effects of using loads ≥ 20% BM and compare them with a novel training stimulus (i.e., BRS). The findings that BRS improved forward sprint performance and that relatively heavy FRS improved vertically oriented tasks (i.e., CMJ height and leg stiffness) indicate a transfer effect for specific sprint training methods exists.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study demonstrate that BRS training is most beneficial in improving athletic performance in youth boys. Although previous studies using FRS training programmes have reported improvements in sprinting performance using loads ≤ 20% BM (2,31,36), the aim of this study was to evaluate the effects of using loads ≥ 20% BM and compare them with a novel training stimulus (i.e., BRS). The findings that BRS improved forward sprint performance and that relatively heavy FRS improved vertically oriented tasks (i.e., CMJ height and leg stiffness) indicate a transfer effect for specific sprint training methods exists.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, minimal loading with sensible upper limits of 10% BM has been recommended for youth (29). Although suggestions have been made to limit RS loads to 10%, it has been shown that training with loads up to 20% results in improved force capabilities and sprinting performance in boys (36). In addition, findings from this research demonstrate that towing weighted sleds ranging from 20 to 55% BM can safely be used to overload BRS and FRS, minimize negative adaptations, and cause meaningful changes in a variety of athletic tasks in mid-PHV to post-PHV boys.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations